2008
DOI: 10.1128/aem.00895-08
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Bifidobacteriaceae from Human Saliva

Abstract: Bifidobacteriaceae were isolated from saliva and infected dentine by using a mupirocin-based selective medium. Of the saliva samples, 94% harbored bifids. The mean concentration (+/- the standard error) was 4.46 (+/-0.12) log(10)(CFU per ml + 1), and the predominant isolates were Bifidobacterium dentium, B. longum, Scardovia inopinata, Parascardovia denticolens, and Alloscardovia omnicolens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 35 publications
2
64
1
1
Order By: Relevance
“…The current study corroborates the finding of the study of Becker et al, which further clarifies its association with dentinal caries, although S. wiggsiae was also detected in early, white spot lesions (3). Bifidobacteriaceae are generally acidogenic and acid tolerant and have been significantly associated with caries in adults by culture (5,34,53) and in children (1,30) and in our studies with severe ECC using PCR (36). In the current study, the combination of S. mutans and S. wiggsiae was highly associated with severe ECC.…”
Section: Vol 49 2011 Culture Of Early Childhood Caries 1471supporting
confidence: 92%
See 1 more Smart Citation
“…The current study corroborates the finding of the study of Becker et al, which further clarifies its association with dentinal caries, although S. wiggsiae was also detected in early, white spot lesions (3). Bifidobacteriaceae are generally acidogenic and acid tolerant and have been significantly associated with caries in adults by culture (5,34,53) and in children (1,30) and in our studies with severe ECC using PCR (36). In the current study, the combination of S. mutans and S. wiggsiae was highly associated with severe ECC.…”
Section: Vol 49 2011 Culture Of Early Childhood Caries 1471supporting
confidence: 92%
“…B. dentium was the major species detected from childhood caries (30) using a selective medium for intestinal bifidobacteria modified for oral samples (5). Another unnamed Bifidobacterium species, HOT 198, was detected in one caries-free child (Fig.…”
Section: Bifidobacteriaceae Lactobacillus and Actinomyces Speciesmentioning
confidence: 99%
“…The available significant rRNA gene sequencing studies pertaining to the oral microbiome is shown in Quantity of these organisms are highly associated with higher number of dental caries associated bacteria (Beighton et al, 2008) (…”
Section: Metagenomic Detection Of the Oral Microbiomementioning
confidence: 99%
“…(6,7) Again, although encouraging results have been observed, most studies have been fairly short. Furthermore, in some studies the observed differences were quite small, though statistically significant.…”
mentioning
confidence: 99%